Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s12034-008-0110-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface morphology on atmospheric corrosion behaviour of Fe-based metallic glass, Fe67Co18Si14B1

Abstract: Abstract. The nature of atmospheric corrosion behaviour of an as-cast metallic glass, Fe 67 Co 18 Si 1 B 14 ribbon, was evaluated. The wheel side surface of the ribbon was more corroded than the air side surface, due to the higher density of air pockets present. The phases present in atmospheric rust were analysed by X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) to be goethite, lepidocrocite, magnetite, cobalt oxide and cobalt hydroxide phases. Goethite and lepidocrocite were in am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…It is noteworthy here that the results of the present investigations are also corroborated by weight loss studies and optical micrographs. Similar investigations are reported by some investigators [7][8]. Dutta et al reported that the wheel side surface of the Ti-Cu ribbon possess inferior corrosion resistance as compared to the air side surface.…”
Section: Discussionsupporting
confidence: 87%
“…It is noteworthy here that the results of the present investigations are also corroborated by weight loss studies and optical micrographs. Similar investigations are reported by some investigators [7][8]. Dutta et al reported that the wheel side surface of the Ti-Cu ribbon possess inferior corrosion resistance as compared to the air side surface.…”
Section: Discussionsupporting
confidence: 87%
“…The oxidation and corrosion behavior of several Zr-based alloys, both in ribbon as well as in bulk form, has earlier been investigated in the author's laboratory [11,12,52]. For a review of the oxidation and corrosion behavior of other important Zr-and Fe-based amorphous alloys reader may refer to reported articles in the literature [15,[68][69][70][71].…”
Section: Introductionmentioning
confidence: 99%